GAMBARAN KETIDAKTERSEDIAAN DOKUMEN REKAM MEDIS RAWAT JALAN DI RSUD DR. SOEKARDJO TASIKMALAYA - Any Octavia Purnama Sari; Tri Purnama Sari; Tesa Herta Pela; Imas Masturoh (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
Good medical records is contain continuous data from the beginning to the end of treatment, so if the medical records unavailable it would disruption many aspects from the patient’s treatment to the payment process. This research aims to describe the unavailability of outpatient medical record in Dr. Soekardjo Tasikmalaya. Mix method sequentional explanatory was used in this research. The amount of samples is 4611 medical records with total sampling technic for two weeks. The results showed there are 22 medical records were not available. The highest unavailability by payment type BPJS 91%, interna clinic 27.3%, and the previous visit on Tuesday, Thursday and Friday are 22.7% each day, during unavaibility occurs on Thursday 36.4%. Filing system used is decentralized, while alignment is middle digit filing with modifications. The cause of the unavailability are limited human resources, inappropriate storage, medical records were taken of patients, limited facilities and infrastructure, eror when writing the number. The impacts are less suitable financing claims, scorching of the claims, the absence of the report claims, the disruption of the patients’s treatment, and patients wait a long time for treatment. There are similarities unavailability of medical records were missing if viewed by the previous visit and when the loss occurs on Thursday. Advised to recording expenditures medical records and color code on the medical records.